Does Shariah Supervisory Board Matter in Explaining Islamic Social Reporting by Indonesian Islamic Commercial Banks? - Rifdah Safinatun Najah; Dita Andraeny (Universitas Airlangga, 2023)
ABSTRACT This study aimed to investigate the impact of Sharia Supervisory Board (SSB) on Islamic Social Responsibility (ISR) by Islamic Commercial Banks in Indonesia. Secondary data were collected from the annual reports of 14 Islamic Commercial Banks in Indonesia from 2010 to 2020, resulting in 125 firm-year data. A panel data regression was applied to analyze the data. The analysis results show that SSB age, cross-membership, and meeting frequency have a positive effect on ISR, whereas size has a negative effect. However, this analysis results did not manage to support the effect of SSB qualifications (Ph.D.) and expertise on ISR. The findings imply that SSB needs to increase the frequency of meetings to improve its supervisory function over Shariah banks' management, including in encouraging more comprehensive ISR disclosure. The contribution of this research is that research focuses on the characteristics of SSB on ISR by using Sharia Enterprise Theory (SET) to provide a better understanding of how these factors influence the implementation of ISR in the sharia context. Keywords: Sharia Supervisory Board Characteristics, Social Reporting, Islamic Bank, Indonesia ABSTRAK Tujuan dari penelitian ini adalah untuk menyelidiki dampak SSB terhadap Islamic Social Reporting (ISR) oleh Bank Umum Syariah di Indonesia. Data sekunder dikumpulkan dari laporan tahunan 14 Bank Umum Syariah di Indonesia sejak 2010 hingga 2020, menghasilkan 125 data firm-year. Regresi data panel diterapkan untuk menganalisis data. Hasil analisis menunjukkan bahwa usia SSB, lintas keanggotaan, dan frekuensi pertemuan berpengaruh positif pada ISR, sedangkan ukuran berpengaruh negatif. Namun hasil analisis ini tidak mendukung pengaruh kualifikasi (Ph.D.) dan keahlian SSB terhadap ISR. Temuan ini menyiratkan bahwa DPS perlu meningkatkan frekuensi pertemuan dalam rangka meningkatkan fungsi pengawasan terhadap manajemen bank syariah, termasuk dalam mmendorong pengungkapan ISR yang lebih komprehensif. kontribusi dalam penelitian ini yaitu Penelitian memfokuskan pada karakteristik SSB terhadap ISR dengan menggunakan Syariah Enterprise Theory (SET) untuk memberikan pemahaman yang lebih baik tentang bagaimana faktor-faktor tersebut mempengaruhi pelaksanaan ISR dalam konteks syariah. Kata Kunci: Karakteristik Dewan Pengawas Syariah, Pelaporan Sosial, Bank Syariah, Indonesia. REFERENCES Abdullah, W. A. W., Percy, M., & Stewart, J. (2013). Shari'ah disclosures in Malaysian and Indonesian Islamic banks The Shari'ah governance system. Journal of Islamic Accounting and Business Research, 4(2), 100–131. doi:10.1108/JIABR-10-2012-0063 Adiertanto, C. P., & Chariri, A. (2013). Analisis Pengaruh islamic corporate governance terhadap corporate social responsibility (Studi kasus pada Bank Syariah di Indonesia). Diponegoro Journal of Accounting. Alam, N., Ramachandran, J., & Nahomy, A. H. (2020). The impact of corporate governance and agency effect on earnings management – A test of the dual banking system. Research in International Business and Finance, 54. doi:10.1016/j.ribaf.2020.101242 Almutair, A. R., & Quttainah, M. A. (2017). Corporate governance